Ultra thin deposited and segregated films - Jenko, Monika (Kovine zlitine tehnologije, 1997)
Research, development and use of vacuum and thin films started at the Institute for Electronics and Vacuum Techniques, IEVT, Ljubljana, after its foundation around 1950. With the development of miniature thin film potentiometers and thin films resistors of high stability at IEVT the first production of thin film electronic components in former Yugoslavia was established. The technology was successfully transferred to Slovenian foreign factory in Cormons Italy where Slovenian minority is living. At the same time the high tech research and development of the second and third generation image intensifier tubes was started. Prof. Dr. Jože Gasperič was one of the leading scientists investigating the sputtered cermet thin films in his BS and Ph.D works.His findings are basic for understanding the mechanism of growth of thin sputtered cermet films. In the middle of the eighties an experimental ultra high vacuum, UHV, system equipped with Auger spectrometer, was built at IEVT and the investigation of physical and chemical processes of ultra thin oxide film growth on the surface of liquid indium and indium alloysin situ was achieved for the first time. The experimental method based on Auger Electron Spectroscopy for in situ investigation of the initial phase of the ultra thin oxide film growth on liquid indium, was developed at the institute. The modified experimental method was also used for the study of ultra thin segregated Sb, Sn or Se films on the surface of FeSiC alloy, microalloyed by Sb, Sn or Se. The investigation of ultra thin Sn, Sb or Se films on well defined Fe surfaces is the topic of our present research which is close connected with the purchase of new AES/XPS instrument with the very high spatial resolution. The results of investigations of ultra thin oxide films on the liquid indium and InSn alloy as well as Sb and Sn ultra thin film growth on the surface of FeSiC alloy were presented.
Keywords: tanke plasti; kovinski oksidi; kovine; segregacija; antimon; antimony; kositer; indij; fizika kondenzirane materije; fizika površin